Catalyst for polyester synthesis and preparation method thereof
By loading the bisimidazole salt ionic liquid on Al/SBA-15, a supported ionic liquid catalyst for polyester synthesis was prepared, which solved the problems of heavy metal pollution and low catalytic efficiency of the existing catalysts, and achieved efficient polyester synthesis and industrial adaptability.
Patent Information
- Application Number
- CN202411823328.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-07
AI Technical Summary
During the polyester synthesis process, existing catalysts have problems such as heavy metal pollution, low catalytic efficiency, high cost, and unfavorable industrialization.
A supported ionic liquid catalyst was prepared for polyester synthesis by loading the bisimidazole salt ionic liquid on Al/SBA-15.
The catalyst has high catalytic activity, can improve the intrinsic viscosity and tensile strength of polyester, reduce heavy metal pollution, and is suitable for industrial production.
Smart Images

Figure BDA0005183605140000031 
Figure BDA0005183605140000032 
Figure BDA0005183605140000041
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and in particular relates to a catalyst for polyester synthesis and a preparation method thereof. Background Art
[0002] Polyester is a kind of polymer material widely used in daily life. Since its birth, it has been continuously improved and developed with many new features, so that it can be applied to some special occasions. It is comparable to or even better than metal materials in terms of mechanical, mechanical, chemical resistance and other properties. Polyester materials with lighter weight characteristics have replaced metal materials in many fields. There are many types of polyesters. According to their uses, they can be divided into fiber-grade, bottle-grade, and film-grade polyesters. Fiber-grade polyesters can be divided into short fibers and filaments. According to the structural units that make up polyester, the common ones are polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), and polyarylate (PAR). Among them, PET not only has good physical and chemical properties but also has cheaper raw materials, so it is widely used in electronics, medical, automobile, construction, packaging, fiber textile and other fields. So far, PET occupies 80% to 90% of the polyester market share, and PET has also become the world's most produced and widely used polyester product.
[0003] Polyethylene terephthalate has a simple molecular structure, and the molecular chain consists of two parts: the end group (carboxyl and hydroxyl) and the repeating unit (the ester benzene ring part of the rigid conjugated system and the -CH2-CH2- of the flexible part). Because its molecule has no side chains, a highly symmetrical structure that can be stacked, a regular molecular chain structure with a rigid benzene ring, it has super rigidity and stability. PET can still maintain good mechanical, insulation, and creep resistance properties in high temperature and high frequency environments. These excellent properties make it less restricted in terms of application areas.
[0004] The preparation methods of polyethylene terephthalate (PET) can be divided into transesterification method (DMT method) and direct esterification method (PTA method) according to the raw materials and synthesis process in the esterification stage.
[0005] In the 1950s and 1960s, when PET production technology was just moving from the laboratory to industrial production, distillation and refining technology was not yet mature, and the purity of terephthalic acid (PTA) on the market was not high enough. The only way was to esterify crude PTA with methanol into dimethyl terephthalate (DMT), then purify DMT, and then transesterify DMT with ethylene glycol (EG) to remove methanol to obtain the ultimate product of the transesterification reaction, diethyl terephthalate (BHET). Although this production method is rarely used now, due to the conditions of the times, the transesterification method was the most important process for synthesizing PET at that time.
[0006] In 1963, Amoco of the United States synthesized high-purity terephthalic acid using a one-step oxidation method and mastered a stable synthesis process technology, which opened a new chapter in the PET polyester production industry. Since the industrialization of the production of purified terephthalic acid (PTA), the DMT method has been eliminated by many polyester production companies, and replaced by the direct esterification method with a simpler and more efficient process. It is obtained by direct esterification of terephthalic acid (PTA) and ethylene glycol (EG), removing small molecules, and then performing high vacuum polymerization.
[0007] Catalysts are the key and difficult issues in the PET production process. In the reaction process, the selection of catalysts is particularly important, which not only affects the reaction rate and the choice of reaction conditions, but also affects the quality of the product, such as molecular weight, color, etc., thereby indirectly affecting the performance and scope of use of the product. At present, in the synthesis process of polyester, the catalysts used are mainly compounds of titanium and antimony. Antimony catalysts such as antimony trioxide, antimony acetate, butanediol antimony and ethylene glycol antimony have the advantages of low cost and few side reactions during the reaction process, but their activity is low, the heavy metals they contain are easy to pollute the environment and the obtained products are easy to appear gray; Germanium catalysts are mainly germanium oxides, germanium esters, etc., which are low in activity and expensive, with few resources, which is not conducive to industrialization; Titanium catalysts have become the research focus of polyester synthesis catalysts in recent years because of their high activity and belonging to an environmentally friendly series of compounds that do not contain heavy metals.
[0008] In view of the many problems existing in the existing technology, such as heavy metal pollution, low catalytic efficiency, high cost, and being unfavorable for industrialization, it is urgent to develop a new catalyst for polyester synthesis suitable for industrial production. Summary of the invention
[0009] In order to achieve the above object, the present invention provides the following specific technical solutions:
[0010] A method for preparing a catalyst for polyester synthesis comprises the following steps:
[0011] Step 1: Synthesis of SBA-15
[0012] Add dilute hydrochloric acid to the reactor, then add the template P123, heat to 30-50°C and stir for 3-10 hours, add ethyl orthosilicate using a tetrafluoroethane constant pressure funnel after P123 is completely dissolved, stir in a water bath and the mixture turns white, then move to a hydrothermal crystallization kettle, take out and cool after 24-48 hours, wash, filter, place the filter cake in a drying oven, dry it, and place it in a high-temperature muffle furnace at 400-700°C and calcine it for 5-10 hours to obtain SBA-15;
[0013] Step 2: Synthesis of Al / SBA-15
[0014] Add aluminum isopropoxide to the n-hexane solution, add the SBA-15 obtained in step 1 after dissolving, stir at room temperature for 5 to 15 hours, and after the reaction is completed, filter, wash, and dry the filter cake, and then place it in a muffle furnace at 400 to 700° C. and calcine it for 5 to 15 hours to obtain Al / SBA-15;
[0015] Step 3: Synthesis of supported ionic liquid catalyst
[0016] Add the Al / SBA-15, bisimidazolium salt ionic liquid and acetonitrile solvent obtained in step 2 into a three-necked flask, heat to 50-80° C. and react for 12-24 hours. After the reaction, evaporate the acetonitrile solvent using a rotary evaporator, and dry the obtained solid in a vacuum drying oven to obtain a supported ionic liquid catalyst;
[0017] The structure of the bisimidazolate ionic liquid is:
[0018]
[0019] In some embodiments, the biimidazole salt ionic liquids A and B are prepared according to the method of the document "Silica Supported and Conventional Approaches for the Synthesis of Carbonyl Diimidazole Type of Ionic Liquids and Its Catalytic Activities", Naveenkumar Ramanathan, et al., J. Heterocyclic Chem., Vol. 2015)", and the following reaction route is used to obtain:
[0020]
[0021] The present invention also protects a catalyst for polyester synthesis, which is prepared according to the above method.
[0022] The invention also protects the use of the catalyst in polyester synthesis.
[0023] In some embodiments, the polyester synthesis comprises the following steps:
[0024] The dibasic acid and diol are subjected to an esterification reaction in the presence of the above catalyst to obtain a prepolymer, and then the prepolymer is subjected to a polycondensation reaction to obtain the polyester.
[0025] In some embodiments, the diacid is one or a combination of at least two of terephthalic acid, isophthalic acid, naphthalene dicarboxylic acid, or adipic acid.
[0026] In some embodiments, the diol is one or a combination of at least two of 1,3-propylene glycol, ethylene glycol, or 1,4-butanediol.
[0027] The present invention has achieved the following beneficial effects:
[0028] 1) The present invention loads a bisimidazolate ionic liquid on Al / SBA-15 to obtain a novel catalyst, which has high catalytic activity. On the one hand, the polyester prepared by the catalyst has a high intrinsic viscosity, and the polyester of the present invention has a larger L and a smaller b value, that is, the product has a better hue. In addition, the introduction of the supported ionic liquid catalyst can greatly improve the tensile strength of the polyester, thereby improving its mechanical properties.
[0029] 2) The use of the catalyst of the present invention can avoid heavy metal pollution, which is conducive to industrial production. DETAILED DESCRIPTION
[0030] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The endpoints and any values of the scope described in the present invention are not limited to the precise scope or value, and these scopes or values should be understood to include values close to these scopes or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be considered as specifically disclosed in this article.
[0032] According to the method of the literature "Silica Supported and Conventional Approaches for the Synthesis of CarbonylDiimidazole Type of Ionic Liquids and Its Catalytic Activities", Naveenkumar Ramanathan, et al., J. Heterocyclic Chem., Vol. 2015), the bisimidazolate ionic liquids A and B were prepared by the following reaction route:
[0033]
[0034] The preparation process is as follows: N,N'-carbonyldiimidazole (0.1 mol) and 1-(bromomethyl)-4-nitrobenzene (0.25 mol) are added to a reactor, and then anhydrous acetonitrile (100 mL) is added, and the temperature is raised to reflux state and stirred for reaction for 12 hours to obtain an intermediate bromide; then the intermediate bromide (0.1 mol) is divided into The inorganic salt (0.25 mol) was stirred in deionized water at room temperature for 1 h to obtain the corresponding salt.
[0035] Bisimidazole salt ionic liquid A:
[0036] 1 HNMR (500MHz, CDCl3): δ=5.80 (s, 4H); 6.45 (dd, 4H); 7.10 (s, 2H); 7.30-7.55 (m, 8H).
[0037] Imidazolium salt ionic liquid B:
[0038] 1 HNMR (500MHz, CDCl3): δ = 5.82 (s, 4H); 6.43 (dd, 4H); 7.12 (s, 2H); 7.35-7.60 (m, 8H).
[0039] Example 1 Preparation of supported ionic liquid catalyst Cat1
[0040] Step 1: Synthesis of SBA-15
[0041] 1.5 mol / L dilute hydrochloric acid (150 mL) was added into the reactor, and then the template P123 (5.0 g) was added. The temperature was raised to 35°C and stirred for 5 h. After P123 was completely dissolved, a certain amount of tetraethyl orthosilicate (TEOs) was added using a tetrafluoroethane constant pressure funnel. After stirring in a water bath for 24 h, the mixture turned white and was subsequently transferred to a 200 mL hydrothermal crystallization kettle. After 48 h, the mixture was taken out and cooled, washed, and filtered. The filter cake was placed in a drying oven, dried for 10 h, and then placed in a 550°C high-temperature muffle furnace for calcination for 6 h to obtain SBA-15.
[0042] Step 2: Synthesis of Al / SBA-15
[0043] 5 g of aluminum isopropoxide (C9H 21 AlO3) was added to 100 mL of n-hexane solution, and after dissolving, 5 g of SBA-15 obtained in step 1 was added, and stirred at room temperature for 12 h. After the reaction was completed, the filter cake was filtered, washed, and dried, and then calcined in a muffle furnace at 550 ° C for 10 h to obtain Al / SBA-15.
[0044] Step 3: Synthesis of supported ionic liquid catalyst Cat1
[0045] 10g of Al / SBA-15, 5g of bisimidazolate ionic liquid A and 100ml of acetonitrile solvent were added to a three-necked flask, and the temperature was raised to 70°C for condensation reflux reaction for 24h. After the reaction, the acetonitrile solvent was evaporated by a rotary evaporator, and the obtained solid was placed in a vacuum drying oven at 100°C and dried for 12h to obtain the supported ionic liquid catalyst Cat1.
[0046] Example 2 Preparation of supported ionic liquid catalyst Cat2
[0047] Step 1: Synthesis of SBA-15
[0048] 1.5 mol / L dilute hydrochloric acid (150 mL) was added into the reactor, and then the template P123 (5.0 g) was added. The temperature was raised to 35°C and stirred for 5 h. After P123 was completely dissolved, a certain amount of tetraethyl orthosilicate (TEOs) was added using a tetrafluoroethane constant pressure funnel. After stirring in a water bath for 24 h, the mixture turned white and was subsequently transferred to a 200 mL hydrothermal crystallization kettle. After 48 h, the mixture was taken out and cooled, washed, and filtered. The filter cake was placed in a drying oven, dried for 10 h, and then placed in a 550°C high-temperature muffle furnace for calcination for 6 h to obtain SBA-15.
[0049] Step 2: Synthesis of Al / SBA-15
[0050] 5 g of aluminum isopropoxide (C9H 21 AlO3) was added to 100 mL of n-hexane solution, and after dissolving, 5 g of SBA-15 obtained in step 1 was added, and stirred at room temperature for 12 h. After the reaction was completed, the filter cake was filtered, washed, and dried, and then calcined in a muffle furnace at 550 ° C for 10 h to obtain Al / SBA-15.
[0051] Step 3: Synthesis of supported ionic liquid catalyst Cat2
[0052] 10g of Al / SBA-15, 5g of bisimidazolate ionic liquid B and 100ml of acetonitrile solvent were added to a three-necked flask, and the temperature was raised to 70°C for condensation reflux reaction for 24h. After the reaction, the acetonitrile solvent was evaporated by a rotary evaporator, and the obtained solid was placed in a vacuum drying oven at 100°C and dried for 12h to obtain the supported ionic liquid catalyst Cat2.
[0053] Application Examples
[0054] Application Example 1 Synthesis of PET polyester
[0055] Put terephthalic acid, ethylene glycol, and Cat1 (molar ratio of 1:1.2:0.1) into a 5L polymerization reactor; then mix and beat at a low speed, and replace with nitrogen three times after sufficient mixing. After the above operation is completed, turn on the heater and increase the speed; control the reaction temperature in the reactor at 240°C. As the esterification reaction proceeds, the esterification byproduct water gradually increases, and the evaporation and gasification of water cause the pressure in the reactor to gradually increase. The pressure in the reactor is controlled at 0.3MPa by the drain valve at the end of the distillation column. When distilled water flows out of the drain valve, the esterification reaction is considered to have begun, and the time is recorded. During this process, relevant information is recorded at regular intervals, and the effluent at the corresponding time point is collected and sealed for storage. When the collected effluent reaches more than 95% of the theoretical water output, the esterification is considered to be completed. Turn on the water circulation vacuum pump to gradually reduce the pressure in the reactor to enter the pre-polycondensation reaction stage. The reaction temperature is controlled at 260°C. This process takes a total of 30 minutes, and then enters the final polycondensation reaction stage. Turn on the high vacuum pump. When the vacuum degree in the reactor reaches below 100Pa, it is considered that the final polycondensation reaction stage begins. As the reactants continue to react, the viscosity of the material in the reactor increases, and the power of the stirring motor increases accordingly. When it reaches a certain wattage, turn off the power, fill the reactor with nitrogen, discharge the material, cool it with water, cut it into pellets, and obtain PET slices for drying and storage.
[0056] Application Example 2 Synthesis of PET polyester
[0057] On the basis of Application Example 1, the supported ionic liquid catalyst Cat1 was replaced by the supported ionic liquid catalyst Cat2, and other conditions were the same.
[0058] Application Comparative Example 1 Synthesis of PET Polyester
[0059] On the basis of Application Example 1, the supported ionic liquid catalyst Cat1 was replaced with a bisimidazolate ionic liquid A, and other conditions were the same.
[0060] Application Comparative Example 2 Synthesis of PET Polyester
[0061] On the basis of Application Example 1, the supported ionic liquid catalyst Cat1 was replaced with a bisimidazolate ionic liquid B, and other conditions were the same.
[0062] Application Comparative Example 3 Synthesis of PET Polyester
[0063] On the basis of Application Example 1, the supported ionic liquid catalyst Cat1 was replaced with ethylene glycol antimony, and other conditions were the same.
[0064] Performance Testing
[0065] The relevant properties of the PET polyesters of the above-mentioned application examples 1-2 and application comparative examples 1-3 were measured, and the measuring methods of each property are as follows:
[0066] 1) Intrinsic viscosity: Phenol-tetrachloroethane with a mass ratio of 6:4 is used as the solvent. The sample is measured in a constant temperature bath at 25°C using an Ubbelohde viscometer. 0.5g of the sample is placed in a 100mL volumetric flask and dissolved. The outflow time of the pure solvent and the solution is measured, and the intrinsic viscosity is calculated according to the formula.
[0067]
[0068] Where: n r is the relative viscosity, c is the solution concentration, and n is the intrinsic viscosity.
[0069] 2) Chroma: After the sample is dried, use a colorimeter to test the sample's chroma. Stack the sample tightly and place it on the measuring hole to measure the sample's chroma (L value, a value, b value). Test it every 120° and measure three points in total. The L value is the whiteness and the b value is the yellowness index. Generally, the larger the L value, the smaller the b value, and the better the product hue.
[0070] 3) Tensile performance test: The PET specimens were tested using an electronic universal testing machine according to GB / T1040.3-2006, with the tensile rate set at 20 mm / min. Each group of samples was tested 3 times on average, and the average value was taken as the test data.
[0071] Table 1 PET performance test
[0072]
[0073] As can be seen from Table 1, the supported ionic liquid catalyst prepared by the present invention has a high catalytic activity. On the one hand, the polyester prepared by the catalyst has a high intrinsic viscosity, and compared with the comparative example, the polyester of the present invention has a larger L value and a smaller b value, that is, the product has a better hue. In addition, the introduction of the supported ionic liquid catalyst can greatly improve the tensile strength of the polyester, thereby improving its mechanical properties.
[0074] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a catalyst for polyester synthesis, comprising the following steps: Step 1: Synthesis of SBA-15 Add dilute hydrochloric acid to the reactor, then add the template P123, heat to 30-50°C and stir for 3-10 hours, add ethyl orthosilicate using a tetrafluoroethane constant pressure funnel after P123 is completely dissolved, stir in a water bath and the mixture turns white, then move to a hydrothermal crystallization kettle, take out and cool after 24-48 hours, wash, filter, place the filter cake in a drying oven, dry it, and place it in a high-temperature muffle furnace at 400-700°C and calcine it for 5-10 hours to obtain SBA-15; Step 2: Synthesis of Al / SBA-15 Add aluminum isopropoxide to the n-hexane solution, add the SBA-15 obtained in step 1 after dissolving, stir at room temperature for 5 to 15 hours, and after the reaction is completed, filter, wash, and dry the filter cake, and then place it in a muffle furnace at 400 to 700° C. and calcine it for 5 to 15 hours to obtain Al / SBA-15; Step 3: Synthesis of supported ionic liquid catalyst Add the Al / SBA-15, bisimidazolium salt ionic liquid and acetonitrile solvent obtained in step 2 into a three-necked flask, heat to 50-80° C. and react for 12-24 hours. After the reaction, evaporate the acetonitrile solvent using a rotary evaporator, and dry the obtained solid in a vacuum drying oven to obtain a supported ionic liquid catalyst; The structure of the bisimidazolate ionic liquid is:
2. A catalyst for polyester synthesis, characterized in that: The catalyst is prepared according to the method according to claim 1.
3. Use of the catalyst according to claim 1 or 2 in polyester synthesis.
4. The use according to claim 3, characterized in that: The polyester synthesis comprises the following steps: The dibasic acid and the diol are subjected to an esterification reaction in the presence of the catalyst described in claim 1 or 2 to obtain a prepolymer, and then the prepolymer is subjected to a polycondensation reaction to obtain the polyester.
5. The use according to claim 4, characterized in that: The dibasic acid is one of terephthalic acid, isophthalic acid, naphthalene dicarboxylic acid or adipic acid, or a combination of at least two of them.
6. The use according to claim 4, characterized in that: The diol is one of 1,3-propylene glycol, ethylene glycol or 1,4-butanediol, or a combination of at least two of them.